Molecular docking unveils prospective inhibitors for the SARS-COV-2 main protease - Ahmad, Fawad; Ikram, Saima; Ahmad, Jamshaid; ur Rehman, Irshad; Khattak, Saeed Ullah; Butt, Sadia; Mushtaq, Maryam (Penerbit Universiti Kebangsaan Malaysia, 2021)
The recent emergence of a novel coronavirus strain (SARS-CoV-2) has stimulated global efforts to identify potential drugs that target proteins expressed by this novel coronavirus. Among these, the main protease of SARS-CoV-2 (3CL-protease (3CLPro), also known as (MPro) is one of the best choices for the scientists to target. 3CLPro is involved in the processing of polyproteins into mature non-structural viral proteins. An X-ray crystallographic structure (PDB ID 6LU7) of this protein was obtained from the PDB database. ChemDiv libraries of ~80,000 antiviral and ~13,000 coronavirus-targeting molecules were screened against the 3D structure of 3CLPro of SARS-CoV-2. We have identified a panel of molecules that showed an activity and potentially block the active site of the SARS-CoV-2 main protease. These molecules can be investigated further to develop effective virus-inhibiting molecules to treat this highly distressing disease, causing extreme unrest across the globe.